The changing epidemiology of bacillary dysentery and characteristics of antimicrobial resistance of Shigella isolated in China from 2004–2014. Issue 1 (December 2016) - Chang, Zhaorui; Zhang, Jing; Ran, Lu; Sun, Junling; Liu, Fengfeng; Luo, Li; Zeng, Lingjia; Wang, Liping; Li, Zhongjie; Yu, Hongjie; Liao, Qiaohong
Abstract Background Bacillary dysentery caused by bacteria of the genusShigella is a significant public health problem in developing countries such as China. The objective of this study was to analyze the epidemiological pattern of bacillary dysentery, the diversity of the causative agent, and the antimicrobial resistance patterns ofShigella spp. for the purpose of determining the most effective allocation of resources and prioritization of interventions. Methods Surveillance data were acquired from the National Infectious Disease Information Reporting System (2004–2014) and from the sentinel hospital-based surveillance system (2005–2014). We analyzed the spatial and temporal distribution of bacillary dysentery, age and sex distribution, species diversity, and antimicrobial resistance patterns ofShigella spp. Results The surveillance registry included over 3 million probable cases of bacillary dysentery during the period 2004–2014. The annual incidence rate of bacillary dysentery decreased from 38.03 cases per 100, 000 person-years in 2004 to 11.24 cases per 100, 000 person-years in 2014. The case-fatality rate decreased from 0.028% in 2004 to 0.003% in 2014. Children aged <1 year and 1–4 years were most affected, with higher incidence rates (228.59 cases per 100, 000 person-years and 92.58 cases per 100, 000 person-years respectively). The annual epidemic season occurred between June and September. A higher incidence rate of bacillary dysentery was found in the Northwest region, Beijing and Tianjin during the study period.Shigella flexneri was the most prevalent species that caused bacillary dysentery in China (63.86%), followed byShigella sonnei (34.89%).Shigella isolates were highly resistant to nalidixic acid (89.13%), ampicillin (88.90%), tetracycline (88.43%), and sulfamethoxazole (82.92%). During the study period, isolates resistant to ciprofloxacin and cefotaxime increased from 8.53 and 7.87% in 2005 to 44.65 and 29.94% in 2014, respectively. Conclusions The incidence rate of bacillary dysentery has undergone an obvious decrease from 2004 to 2014. Priority interventions should be delivered to populations in northwest China and to individuals aged <5 years. Antimicrobial resistance ofShigella is a serious public health problem and it is important to consider the susceptibility profile of isolates before determining treatment.